The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12933-016-0435-0
|View full text |Cite
|
Sign up to set email alerts
|

Variant rs10911021 that associates with coronary heart disease in type 2 diabetes, is associated with lower concentrations of circulating HDL cholesterol and large HDL particles but not with amino acids

Abstract: AimsAn intergenic locus on chromosome 1 (lead SNP rs10911021) was previously associated with coronary heart disease (CHD) in type 2 diabetes (T2D). Using data from the UCLEB consortium we investigated the relationship between rs10911021 and CHD in T2D, whether rs10911021 was associated with levels of amino acids involved in the γ-glutamyl cycle or any conventional risk factors (CRFs) for CHD in the T2D participants.MethodsFour UCLEB studies (n = 6531) had rs10911021 imputation, CHD in T2D, CRF and metabolomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Our results showed that 2 SNPs (rs2285666 and rs4646142) was not associated with T2D (see Additional file 1 : Table S4) but exhibited association with T2D with moderate risk of atherogenic dyslipidemia (see Additional file 1 : Table S6, S7), which were consistent with previously reported association of the loci with ASCVD (e.g., coronary heart disease [ 32 ], ischemic stroke [ 33 ]) in T2D patients as well as cardiovascular death in European females [ 34 ]. Similar effects also existed in between rs10911021 and CAD in T2D [ 35 ] as well as between CLOCK polymorphism and stroke in T2D patients [ 36 ]. According to the 2014 NLA recommendations [ 37 ], carotid arteriosclerosis stenosis (CAS) ≥ 50% is defined as a new type of ASCVD.…”
Section: Discussionmentioning
confidence: 67%
“…Our results showed that 2 SNPs (rs2285666 and rs4646142) was not associated with T2D (see Additional file 1 : Table S4) but exhibited association with T2D with moderate risk of atherogenic dyslipidemia (see Additional file 1 : Table S6, S7), which were consistent with previously reported association of the loci with ASCVD (e.g., coronary heart disease [ 32 ], ischemic stroke [ 33 ]) in T2D patients as well as cardiovascular death in European females [ 34 ]. Similar effects also existed in between rs10911021 and CAD in T2D [ 35 ] as well as between CLOCK polymorphism and stroke in T2D patients [ 36 ]. According to the 2014 NLA recommendations [ 37 ], carotid arteriosclerosis stenosis (CAS) ≥ 50% is defined as a new type of ASCVD.…”
Section: Discussionmentioning
confidence: 67%
“…Genome-wide association studies have provided good insight into the relationship between lipid metabolism and CAD [ 22 , 23 ]. From these studies the cardiovascular phenotype of genetic variants seems to depend on ethnicity or the presence of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies confirmed the association of the rs10911021 GLUL variant with type 2 DM, and demonstrated that this polymorphism does not affect amino acid metabolism. However, although apparently counterintuitive, it is associated with lower HDL cholesterol levels, and large HDL particles ( 45 ).…”
Section: Genetic Aspectsmentioning
confidence: 99%